WOMEN, EDUCATION, AND EMPLOYMENT: CHALLENGES AND OPPORTUNITIES IN ISLAMIC HIGHER EDUCATION - Sahliah Sahliah; Watni Marpaung (Journal of Gender and Social Inclusion in Muslim Societies, 2022)
The findings indicate that many alumni are employed in fields not directly related to their academic specialization. Contributing factors to this trend include limited job market opportunities that align with the program's focus and inadequate integration of practical training throughout their studies. Stakeholders recognize strengths among alumni, such as adaptability and commitment, but they also emphasize the necessity for curriculum enhancements aimed at improving job readiness. This research investigates the alumni tracking of the Muamalah Study Program within the Faculty of Sharia and Law at Universitas Islam Negeri Sumatera Utara. The primary objective is to analyze employment patterns among alumni and their correspondence with the academic outcomes of the program. Data were collected through in-depth interviews, observations, and content analysis of stakeholders' perceptions and alumni experiences. The results reveal a significant number of alumni securing employment outside their academic fields. Factors contributing to this situation include a scarcity of job market opportunities that align with the program's focus and insufficient practical training during their academic tenure. Stakeholders highlighted alumni strengths, including adaptability and commitment, while stressing the need for curriculum improvements to enhance job readiness. This study underscores the importance of strengthening the alumni network and establishing institutional partnerships to bridge the gap between academic training and employment opportunities. Based on our findings, we offer recommendations aimed at improving alumni outcomes and better aligning them with the objectives of the Muamalah Study Program